Integrated Free-Space Optics and Fiber Optic Network Performance Enhancement for Sustaining 5G High Capacity Communications - Alsharari, Meshari; Aliqab, Khaled; Ali, Farman; Armghan, Ammar (International Journal of Optics, 2023)
In this paper, the integrated free-space optics (FSO) and fiber optic model is evaluated using new radio (NR) sub-THz link to sustain next generation 5G capacity. The proposed integrated model effectively applies over 25 km single mode fiber, 0.5 m RF wireless, and 500 m optical wireless. In addition, four different sub-THz frequencies (125, 150, 175, and 200 GHz) are estimated on NR-based 5G FSO network, including 22 Gbps 64quadrature amplitude modulation-orthogonal frequency division multiplexing (64QAM-OFDM) signal speed. The proposed FSO enabled fiber optic system is also measured mathematically to satisfy the data transmission accuracy. For confirmation, the theoretical approach of the presented FSO and fiber optic network is realized with an aggregate 342 Gbps speed 16×22. The performance metrics comprising forward error limit (FEL), bit error rate (BER), and error vector magnitude (EVM) are used for weighing simulation results. The outlets of an integrated fiber-FSO network show that by applying NR 5G sub-THz, a high data rate with multiple inputs and multiple outputs (MIMO) transmission capacity can be adjusted victoriously.